Analisis Program Bantuan Stimulan Perumahan Swadaya (BSPS) Terhadap Tingkat Kepuasan Masyarakat Berpenghasilan Rendah Pada Kantor Dinas Perumahan Rakyat Kawasan Pemukiman Dan Pertanahan Kabupaten Ende Tahun Anggaran 2017 - Timbu, Maria Alfonsa Rima; Langga, Lambertus; Tanusi, Gabriel (Program Studi Manajemen Universitas Flores, 2021)
Meeting the needs of a decent home for a weak economic community,government through the Public Housing Agency, Residential Areas and Ende District Land Issued a policy with the development and utilization of potential community empowerment through home rehabilitation is not livable.From the results of the study it was found that in general the Help program Self-Help Housing Stimulant (BSPS) has satisfied the community Low-income. Of the fourteen variables studied, the value of the IKM variable service procedure of 78.0%, variable discipline of officers service by 72.5%, variable clarity of service personnel by 74.2%, service officer's responsibility variable of 74.4%, variable capability service personnel by 72.5%, variable service speed by 70.9%, variable justice gets service by 72.5%, variable decency and 71.7%, variable fairness of service costs amounting to 69.0%, variable service cost certainty of 63.0%, convenience variable 73.9%, and service security variables by 71.7%. Two twelve variables are categorized as satisfactory because they are all at intervals 62,51% – 81,25%. IKMvariable service requirements of 83.4% and highly to satisfy low-income communities. Thirteen satisfying variables Community. Obtainedik M variable certainty of service schedule amounting to 51.6% were categorized as unsatisfactory due to the 43.76% interval –62,50%.